Integración del proyecto ambiental escolar (PRAE), el plan institucional de gestión ambiental (PIGA) y la ISO 14001 en el colegio distrital Ciudad de Villavicencio de Bogotá (2019)
The research project presented below was aimed to structure and deliver a proposal for integration of the Institutional Plan for Environmental Management (Plan Institucional de Gestión Ambiental, PIGA) Decree 456 of 2008, with the School Environmental Project (Proyecto Ambiental Escolar, PRAE) Decree 1743 of 1994, based on compliance with the requirements of ISO 14001:2015 in the Ciudad de Villavicencio District School. The research process is framed in the concepts of environmental education, environmental management, systemic thinking and management systems integration. As part of the methodological design, the review of compliance with the requirements of the environmental standard was proposed, which allowed to identify the common requirements of PIGA and PRAE, with ISO 14001. The main finding is the disarticulation of PIGA and PRAE, specifically in the construction of documents and the planning and execution of activities, which limits decision making and the generation of actions that allow a better environmental management of the school. Based on the above and under the parameters of integration by common requirements through the Plan, Do, Verify and Act cycle (Planear, Hacer, Verificar, Actuar; PHVA), an integration proposal is developed, having as scope the requirements alignment of PRAE and PIGA with the high level structure of ISO 14001:2015. The importance of this research lies in demonstrating that compliance with the management systems requirements is anticipating in planning, efficient in execution and effective in control and improvement